Relation between the behaviors of P-wave and QT dispersions in elderly patients with heart failure - Szlejf,Cláudia (2002)
OBJECTIVE: To assess the relation between P-wave and QT dispersions in elderly patients with heart failure. METHODS: Forty-seven elderly patients (75.6±6 years) with stable heart failure in NYHA functional classes II or III and with ejection fractions of 37±6% underwent body surface mapping to analyze P-wave and QT dispersions. The degree of correlation between P-wave and QT dispersions was assessed, and P-wave dispersion values in patients with QT dispersion greater than and smaller than 100 ms were compared. RESULTS: The mean values of P-wave and QT dispersions were 54±14 ms and 68±27 ms, respectively. The correlation between the 2 variables was R=0.41 (p=0.04). In patients with QT dispersion values > 100 ms, P-wave dispersion was significantly greater than in those with QT dispersion values < 100 ms (58±16 vs 53±12 ms, p=0.04 ). CONCLUSION: Our results suggest that, in elderly patients with heart failure, a correlation between the values of P-wave and QT dispersions exists. These findings may have etiopathogenic, pathophysiologic, prognostic, and therapeutic implications, which should be investigated in other studies.